CPS architecture design for urban roadway intersections based on MBSE - Chen Wang; Xiaoping Ma; Limin Jia; Zheng Lai; Zhexuan Yang; Han Yan; Jing Zhao (Journal of Intelligent and Connected Vehicles)
With the rapid growth of urbanization and the increasing demand for transportation, urban traffic congestion has become a hindrance to individuals’ travel experience. Urban intersections are one of the primary sources of traffic congestion, and these bottlenecks have a negative impact not only on traffic efficacy but also on the surrounding road traffic in the region. To alleviate urban traffic congestion, cyber-physical systems have been widely implemented in the transportation industry, allowing for the perception, analysis, calculation, and dispatching of urban traffic flow, as well as making urban transportation safe, efficient, and quick. As the system scale and functions increase, system design has become increasingly complex, necessitating a deeper comprehension of the system’s structure and interaction relationships to construct a stable and reliable system. Therefore, this study proposes a method for designing cyber-physical systems for urban traffic intersections based on Model-Based Systems Engineering (MBSE). This method models and analyses exhaustively the system’s requirements, functions, and logical architecture using System Modeling Language (SysML). After the architecture design has been completed, an architecture verification and optimization method based on Failure Mode and Effect Analysis (FMEA) for urban road intersection cyber-physical systems is utilized to analyze the architecture’s reliability by analyzing the failure modes of activities and to optimize the system architecture to improve the design’s efficiency and reliability.